Kredit Bermasalah Dan Administrasi Pinjaman Dalam Perspektif Asymmetric Information Theory Pada Ksp Obor Mas Cabang Pasar Alok - Santa, Maria Dwi; Sanga , Konstantinus Pati; De Romario , Fransiscus (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze loan administration practices and the causes of non-performing loans from the perspective of Asymmetric Information Theory at KSP Kopdit Obor Mas Pasar Alok Branch. This research employs a qualitative descriptive approach using observation, interviews, and documentation as data collection techniques. The results indicate that loan administration has not been optimally implemented, particularly in documentation completeness, creditworthiness analysis, and post-disbursement monitoring. From the asymmetric information perspective, adverse selection and moral hazard were identified as major contributors to non-performing loans. Limited borrower information, misuse of loan funds, and weak supervision were the dominant factors affecting credit quality. The study concludes that improving loan administration systems and strengthening monitoring mechanisms can reduce asymmetric information impacts and minimize non-performing loans in cooperatives.